Anti-light projection film for side projection

By designing a structural layer with cross-change angles and an aluminum-plated reflective layer in the light-resistant projection film, the problems of uneven brightness and low light utilization in the side projection projection are solved, and a higher uniformity and contrast of the projection film are achieved.

CN119644664AInactive Publication Date: 2025-03-18CCS (SHANGHAI) FUNCTIONAL FILMS IND CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411866098.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, in side projection projection, the light source is inversely proportional to the distance between the projection screen, resulting in uneven brightness on the left and right screens, and the light utilization rate of the matte structure is low, too much light scattering, and the more reflected light scattering, the lower the gain of the projection film center.

Method used

A light-resistant projection film is used, and its structure is a matte surface layer, polyethylene terephthalate, structural layer, aluminum-plated reflective layer, black light absorbing layer and polyethylene terephthalate from top to bottom. The structural layer is a special structure with cross-angle changes, and is formed by engraving and sandblasting of copper layers to improve the reflection direction of light, and improve the contrast and light utilization through aluminum plating and black absorbing layers.

Benefits of technology

It is realized that the uniformity and contrast of the projection film are improved without changing the position of the projector, and the utilization rate of the projection film on light is enhanced, and the problems of uneven brightness and low light utilization rate in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119644664A_ABST
    Figure CN119644664A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-light projection film for side projection, and relates to the technical field of projection films. According to the invention, the structure with the crossed change angles is engraved on the surface of the copper layer, so that the incident light of the side projection projector is reflected towards a specified direction, and the uniformity of the projection film is improved; irregular pits are formed in the surface of the structure through a sand blasting machine, so that the reflection loss of light is reduced, the utilization rate of light rays is improved, and the projection benefit of the projection film is increased; after a special structure is transferred to polyester through UV transfer printing, the surface of the polyester is aluminized, and a part of light input by a projector is reflected, so that the black position performance of a picture is improved, and the contrast ratio of the diaphragm is improved; a black light absorption layer covers the projection film, so that the brightness contrast of the bright part and the dark part is increased, and the contrast of the projection film is further improved; and finally, the polyester sealing layer is bonded, and the polyester surface layer connected with the special structure is atomized again to form a rough structure, so that a part of light is reflected in a manner similar to mirror reflection, and the uniformity of the projection film is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of projection films, in particular to a light-resistant projection film used for side projection. Background Art

[0002] With the growing development of electronic audio-visual technology, in the context of LCD TVs being caught in a price war and OLED TVs being well-received but not popular, laser TVs have "accidentally" detonated the high-end large-screen market and become the first choice for many consumers to upgrade. According to data from China Market Research Group from January to October 2023, the sales volume of laser TVs in China's large-screen TV market of 80 inches and above reached 49.05%, and an era of large-screen consumption dominated by laser TVs has quietly arrived. The future attributes of laser TVs, to be precise, are aimed at the entire "color TV large-screen" circle of influence, and this market space is a large market at the level of millions of units. In the field of large-size color TVs, laser TVs can enjoy the dividends of the market explosion and also have a monopolistic independent market segment. This is why industry giants are optimistic about this product line.

[0003] The projection screen is one of the essential accessories for laser TV display. Whether it is traditional projection, smart projection, or laser TV, light is used to project the image onto the screen or wall, and then the screen or wall reflects it into our eyes, becoming the image we see. However, in some special projection venues, the projector needs to be placed sideways. However, because the illumination of the projector is inversely proportional to the distance between the light source and the projection screen, side projection will cause uneven brightness on the left and right sides of the picture. The existing technology usually uses a uniform atomization treatment on the surface of the screen, and uses diffuse reflection to increase the scattering degree of the reflected light from the projection screen to achieve the side projection effect of the projector. However, the matte structure (surface haze is about 90%) has low light utilization, and the light is scattered in all directions. The more the reflected light is scattered, the lower the center gain of the projection film. Summary of the invention

[0004] The object of the present invention is to provide an anti-light projection film for side projection, which ensures that the gain of the projection film can meet the requirements and allows the projector to be projected without being placed in the middle.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an anti-light projection film for side projection, the structure from top to bottom is a matte surface layer, polyethylene terephthalate, a structural layer, an aluminum-plated reflective layer, a black light-absorbing layer, and polyethylene terephthalate, characterized in that the structural layer is a special structure with cross-angle changes, which allows the incident light of the projector to be reflected in a specified direction. The above structure can be applied to the back structure of the laser projection screen, and the laser projection film can achieve side head projection and have a certain anti-light effect through the special design of the surface structure.

[0006] Furthermore, the matte layer is a rough structure with a surface haze of 40 to 60%.

[0007] Furthermore, the structural layer is firstly prepared by engraving structures adjacent to each other at a certain angle on the surface of the copper layer, then atomizing and sandblasting, and finally UV transfer printing on polyethylene terephthalate.

[0008] Furthermore, the thickness of the aluminum-plated reflective layer is 100-200 nm, and the light transmittance is 60%-80%.

[0009] Furthermore, the anti-light projection film comprises the following preparation steps:

[0010] (1) The copper base roller is mounted on an ultra-precision processing machine, cleaned and polished, and then a tool with an angle of 100-120° and an R value of 5-10 μm is used to engrave structures adjacent to each other at an angle on the surface of the copper base roller. The engraving is repeated until the base roller is completely covered. The base roller is then atomized for 5-25 minutes using a sandblasting machine to obtain a mold with a special structure.

[0011] (2) After applying UV glue on the surface of the mold with a special structure, a clean polyethylene terephthalate film is tightly attached to the mold surface, and after no bubbles are present, it is cured with ultraviolet light for 30 to 50 minutes, polished, and placed in a vacuum coating machine, evacuated to a vacuum degree of 0.01 to 0.02 Pa, and aluminum is plated on the surface of the special structure to obtain an aluminum-plated film;

[0012] (3) placing the aluminum-plated film in a mold with shielding on all sides, filling it with black UV glue to a glue layer height of 150 to 200 μm, curing it under ultraviolet light for 2 to 4 hours, and then hot-pressing a cleaned polyethylene terephthalate film on the surface at 100 to 150° C. to obtain a projection film;

[0013] (4) With the polyethylene terephthalate surface of the projection film connected with the special structure facing upward, apply the atomized adhesive to a height of 180-260 μm, and cure at 50-60° C. for 14-28 hours to obtain an anti-light projection film for side projection. The surface of the present invention is uniformly atomized to increase the scattering degree of the reflected light of the projection screen by diffuse reflection, thereby achieving the side projection effect of the projector.

[0014] Furthermore, the sandblasting material in the sandblasting machine in step (1) is 30 μm glass beads and the sandblasting pressure is 0.2 to 0.7 MPa.

[0015] Furthermore, the thickness of the polyethylene terephthalate film in step (2) is 200 to 300 μm.

[0016] Furthermore, the polyethylene terephthalate film in step (3) has a thickness of 220 to 280 μm.

[0017] Furthermore, the preparation step of the atomized adhesive in step (4) is as follows: 100 parts of PU-1750 polyurethane adhesive and 40 to 60 parts of nano-silicon dioxide are mixed at 200 rpm for 3 to 5 hours to obtain the atomized adhesive.

[0018] Furthermore, the particle size of the nano-silicon dioxide is 20 to 40 nm.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The present invention first engraves a structure with a cross-changing angle on the surface of the copper layer, so that the incident light of the side projection projector is reflected in a specified direction, thereby improving the utilization rate of the projection film far from the projector for the light and improving the uniformity of the projection film; then the surface of the structure is atomized by a sandblasting machine, and the sandblasting machine sprays fine sand of glass bead sand material, and the continuous glass bead sand material evenly hits the surface of the micro-concave structure to form irregular pits, so that the light is scattered multiple times on the surface, and the reflection loss of the light is reduced, thereby increasing the propagation path of the light and the interaction between the light and the material, improving the utilization rate of the light, and increasing the projection benefit of the projection film; and then after the special structure is transferred to the polyester by UV transfer, the surface of the Aluminum plating, when the ambient light is strong, reflects part of the light projected by the projector, increases the black level performance of the picture, makes the black deeper, thereby reducing the impact of ambient light and improving the contrast of the film; then it is covered with a layer of black light-absorbing layer, which can effectively absorb the stray light in the environment, thereby making the brightness contrast between the bright and dark parts more obvious, further improving the contrast of the projection film; finally, the polyester sealing layer is bonded, and the polyester surface layer with a special structure is atomized again, so that a rough structure with a haze of 40-60% is formed on its surface, reducing the change in the reflected light spectrum, and making part of the light reflected in a manner similar to mirror reflection, so that the reflected light has a certain directionality, further improving the uniformity of the projection film. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0022] Figure 1 It is a schematic diagram of the structure of the light-resistant projection film prepared by the present invention.

[0023] Figure 2 It is a schematic diagram of the angle of engraving on the surface of the copper-based roller by using a tool in the present invention.

[0024] Figure 3 It is a schematic diagram of the path of engraving on the surface of the copper-based roller by a tool of the present invention.

[0025] Figure 4The present invention is a schematic diagram of the side projection use of the light-resistant projection film prepared by the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the anti-light projection film for side projection prepared in the following examples are as follows:

[0028] Surface structure haze: Take examples of the same size, place them on the test bench of the haze meter, start the measurement program, and the haze meter will automatically measure and record the haze value of the sample.

[0029] Transmittance after aluminum plating: Take examples of the same size and put them into the sample holder of the test instrument, ensure that the sample is perpendicular to the light path and fits tightly to avoid light leakage, start the test program, the instrument automatically measures and records the light intensity passing through the curtain, select different positions for multiple measurements, and record the average value.

[0030] Projection film gain: Take an embodiment of the same size and use a side projection projector to project onto a projection film, and calculate the projection film gain using the following formula.

[0031] Gain = 3.14*projection film surface brightness / projection film surface illumination

[0032] Uniformity: Take examples of the same size and project them onto a projection film using a side projector, and calculate the uniformity using the following formula.

[0033] Uniformity = (sum of the brightness of the two sides of the projection film / 2*the brightness of the center surface of the projection film)

[0034] Example 1

[0035] (1) The copper base roller was mounted on an ultra-precision processing machine, cleaned and polished, and then repeatedly engraved with a tool with an angle of 100° and an R value of 5 μm until the base roller was completely covered. Subsequently, the base roller was atomized for 5 min using a sandblasting machine with a blasting material of 30 μm glass beads and a blasting pressure of 0.2 MPa to obtain a mold with a special structure;

[0036] (2) After UV glue is applied to the surface of the mold with a special structure, a clean polyethylene terephthalate film with a thickness of 200 μm is tightly attached to the surface of the mold, and after no bubbles are present, it is cured with ultraviolet light for 30 minutes, polished, and placed in a vacuum coating machine, evacuated to a vacuum degree of 0.01 Pa, and aluminum is plated on the surface of the special structure to obtain an aluminum-plated film;

[0037] (3) placing the aluminum-plated film in a mold with shielding on all sides, filling it with black UV glue until the glue layer is 150 μm high, curing it under ultraviolet light for 2 hours, and then hot-pressing a cleaned polyethylene terephthalate film with a thickness of 220 μm on the surface at 100° C. to obtain a projection film;

[0038] (4) 100 parts of PU-1750 polyurethane adhesive and 40 parts of nano-silicon dioxide with a particle size of 20 nm were mixed at 200 rpm for 3 hours to prepare an atomized adhesive;

[0039] (5) With the polyethylene terephthalate surface of the projection film connected with the special structure facing upward, atomized adhesive is applied to a height of 180 μm, and the film is cured at 50° C. for 14 h to obtain an anti-light projection film for side projection.

[0040] Example 2

[0041] (1) The copper base roller was mounted on an ultra-precision processing machine, cleaned and polished, and then repeatedly engraved with a tool having an angle of 110° and an R value of 8 μm until the base roller was completely covered. Subsequently, the base roller was atomized for 15 min using a sandblasting machine with a blasting material of 30 μm glass beads and a blasting pressure of 0.45 MPa to obtain a mold with a special structure;

[0042] (2) After applying UV glue on the surface of the mold with a special structure, a clean polyethylene terephthalate film with a thickness of 250 μm is tightly attached to the surface of the mold, and after no bubbles are present, it is cured with ultraviolet light for 40 minutes, polished, placed in a vacuum coating machine, and evacuated to a vacuum degree of 0.015 Pa, and aluminum is plated on the surface of the special structure to obtain an aluminum-plated film;

[0043] (3) placing the aluminum-plated film in a mold with shielding on all sides, filling it with black UV glue until the glue layer is 175 μm high, curing it under ultraviolet light for 3 hours, and then hot-pressing a cleaned polyethylene terephthalate film with a thickness of 250 μm on the surface at 125° C. to obtain a projection film;

[0044] (4) 100 parts of PU-1750 polyurethane adhesive and 50 parts of nano-silicon dioxide with a particle size of 30 nm were mixed at 200 rpm for 4 hours to prepare an atomized adhesive;

[0045] (5) With the polyethylene terephthalate surface of the projection film connected with the special structure facing upward, atomized adhesive was applied to a height of 220 μm, and the film was cured at 55° C. for 21 h to obtain an anti-light projection film for side projection.

[0046] Example 3

[0047] (1) The copper base roller was mounted on an ultra-precision processing machine, cleaned and polished, and then repeatedly engraved with a tool with an angle of 120° and an R value of 10 μm until the base roller was completely covered. Subsequently, the base roller was atomized for 25 minutes using a sandblasting machine with a blasting material of 30 μm glass beads and a blasting pressure of 0.7 MPa to obtain a mold with a special structure;

[0048] (2) After applying UV glue on the surface of the mold with a special structure, a clean polyethylene terephthalate film with a thickness of 300 μm is tightly attached to the surface of the mold, and after no bubbles are present, it is cured with UV light for 50 min, polished, placed in a vacuum coating machine, and evacuated to a vacuum degree of 0.02 Pa, and aluminum is plated on the surface of the special structure to obtain an aluminum-plated film;

[0049] (3) placing the aluminum-plated film in a mold with shielding on all sides, filling it with black UV glue to a glue layer height of 200 μm, curing it under ultraviolet light for 4 hours, and then hot-pressing a cleaned polyethylene terephthalate film with a thickness of 280 μm on the surface at 150° C. to obtain a projection film;

[0050] (4) 100 parts of PU-1750 polyurethane adhesive and 60 parts of nano-silicon dioxide with a particle size of 40 nm were mixed at 200 rpm for 5 hours to prepare an atomized adhesive;

[0051] (5) With the polyethylene terephthalate surface of the projection film connected with the special structure facing upward, atomized adhesive is applied to a height of 260 μm, and the film is cured at 60° C. for 28 h to obtain an anti-light projection film for side projection.

[0052] Example 4

[0053] (1) The copper base roller was mounted on an ultra-precision processing machine, cleaned and polished, and then repeatedly engraved with a tool having an angle of 105° and an R value of 6 μm until the base roller was completely covered. Subsequently, the base roller was atomized for 8 min using a sandblasting machine with a blasting material of 30 μm glass beads and a blasting pressure of 0.3 MPa to obtain a mold with a special structure;

[0054] (2) After applying UV glue on the surface of the mold with a special structure, a clean polyethylene terephthalate film with a thickness of 225 μm is tightly attached to the surface of the mold, and after no bubbles are found, it is cured with ultraviolet light for 35 minutes, polished, placed in a vacuum coating machine, and evacuated to a vacuum degree of 0.012 Pa, and aluminum is plated on the surface of the special structure to obtain an aluminum-plated film;

[0055] (3) placing the aluminum-plated film in a mold with shielding on all sides, filling it with black UV glue until the glue layer is 165 μm high, curing it under ultraviolet light for 2.5 hours, and then hot-pressing a cleaned polyethylene terephthalate film with a thickness of 230 μm on the surface at 115° C. to obtain a projection film;

[0056] (4) 100 parts of PU-1750 polyurethane adhesive and 45 parts of nano-silicon dioxide with a particle size of 25 nm were mixed at 200 rpm for 3.5 hours to prepare an atomized adhesive;

[0057] (5) With the polyethylene terephthalate surface of the projection film connected with the special structure facing upward, atomized adhesive was applied to a height of 200 μm, and the film was cured at 52° C. for 17 h to obtain an anti-light projection film for side projection.

[0058] Example 5

[0059] (1) The copper base roller was mounted on an ultra-precision processing machine, cleaned and polished, and then repeatedly engraved with a tool having an angle of 115° and an R value of 9 μm until the base roller was completely covered. Subsequently, the base roller was atomized for 20 minutes using a sandblasting machine with a blasting material of 30 μm glass beads and a blasting pressure of 0.6 MPa to obtain a mold with a special structure;

[0060] (2) After applying UV glue on the surface of the mold with a special structure, a clean polyethylene terephthalate film with a thickness of 275 μm is tightly attached to the surface of the mold, and after no bubbles are present, it is cured with ultraviolet light for 45 minutes, polished, and placed in a vacuum coating machine, evacuated to a vacuum degree of 0.018 Pa, and aluminum is plated on the surface of the special structure to obtain an aluminum-plated film;

[0061] (3) placing the aluminum-plated film in a mold with shielding on all sides, filling it with black UV glue until the glue layer is 185 μm high, curing it under ultraviolet light for 3.5 hours, and then hot-pressing a cleaned polyethylene terephthalate film with a thickness of 275 μm on the surface at 135° C. to obtain a projection film;

[0062] (4) 100 parts of PU-1750 polyurethane adhesive and 55 parts of nano-silicon dioxide with a particle size of 35 nm were mixed at 200 rpm for 4.5 hours to prepare an atomized adhesive;

[0063] (5) With the polyethylene terephthalate surface of the projection film connected with the special structure facing upward, atomized adhesive was applied to a height of 240 μm, and the film was cured at 57° C. for 25 h to obtain an anti-light projection film for side projection.

[0064] Effect example

[0065] Table 1 below shows the performance analysis results of the anti-glare projection films for side projection use using Examples 1 to 5 of the present invention.

[0066] Table 1

[0067] Surface structure haze Transmittance after aluminum plating Projection film gain Uniformity Pitch Example 1 40% 60% 1.2 65% 120μm Example 2 50% 70% 1.3 70% 120μm Example 3 60% 80% 1.1 80% 120μm Example 4 45% 65% 1.2 75% 120μm Example 5 55% 75% 1.1 75% 120μm

[0068] From the comparison of the experimental data of Examples 1-5 of the present application, it can be found that the anti-light projection film for side projection prepared in the present application has good uniformity while ensuring gain.

[0069] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A light-resistant projection film for side projection, which comprises, from top to bottom, a matte surface layer, polyethylene terephthalate, a structural layer, an aluminum-plated reflective layer, a black light-absorbing layer, and polyethylene terephthalate, wherein: The structural layer is a special structure with a changing angle, which serves to reflect the incident light of the projector in a specified direction.

2. The anti-light projection film for side projection according to claim 1, characterized in that: The matte layer is a rough structure with a surface haze of 40-60%.

3. The anti-light projection film for side projection according to claim 1, characterized in that: The structural layer is firstly prepared by engraving structures adjacent to each other on the surface of the copper layer with a certain angle, then atomizing and sandblasting, and finally UV transfer printing on polyethylene terephthalate.

4. The anti-light projection film for side projection according to claim 1, characterized in that: The thickness of the aluminum-plated reflective layer is 100-200 nm, and the light transmittance is 60%-80%.

5. The anti-light projection film for side projection according to claim 1, characterized in that: The light-resistant projection film comprises the following preparation steps: (1) The copper base roller is mounted on an ultra-precision processing machine, cleaned and polished, and then a tool with an angle of 100-120° and an R value of 5-10 μm is used to engrave structures adjacent to each other at an angle on the surface of the copper base roller. The engraving is repeated until the base roller is completely covered. The base roller is then atomized for 5-25 minutes using a sandblasting machine to obtain a mold with a special structure. (2) After applying UV glue on the surface of the mold with a special structure, a clean polyethylene terephthalate film is tightly attached to the mold surface, and after no bubbles are present, it is cured with ultraviolet light for 30 to 50 minutes, polished, and placed in a vacuum coating machine, evacuated to a vacuum degree of 0.01 to 0.02 Pa, and aluminum is plated on the surface of the special structure to obtain an aluminum-plated film; (3) placing the aluminum-plated film in a mold with shielding on all sides, filling it with black UV glue to a glue layer height of 150 to 200 μm, curing it under ultraviolet light for 2 to 4 hours, and then hot-pressing a cleaned polyethylene terephthalate film on the surface at 100 to 150° C. to obtain a projection film; (4) With the polyethylene terephthalate surface of the projection film connected with the special structure facing upward, atomized adhesive is applied to a height of 180 to 260 μm, and the film is cured at 50 to 60° C. for 14 to 28 hours to obtain a light-resistant projection film for side projection.

6. The anti-light projection film for side projection according to claim 5, characterized in that: The sandblasting material in the sandblasting machine of step (1) is 30 μm glass beads and the sandblasting pressure is 0.2 to 0.7 MPa.

7. The anti-light projection film for side projection according to claim 5, characterized in that: The thickness of the polyethylene terephthalate film in step (2) is 200 to 300 μm.

8. The anti-light projection film for side projection according to claim 5, characterized in that: The thickness of the polyethylene terephthalate film in step (3) is 220 to 280 μm.

9. The anti-light projection film for side projection according to claim 5, characterized in that: The preparation step of the atomized adhesive in step (4) is as follows: 100 parts of PU-1750 polyurethane adhesive and 40 to 60 parts of nano-silicon dioxide are mixed at 200 rpm for 3 to 5 hours to obtain the atomized adhesive.

10. The anti-light projection film for side projection according to claim 9, characterized in that: The particle size of the nano silicon dioxide is 20-40 nm.

Citation Information

Patent Citations

  • Anti-light screen and preparation method thereof

    CN108873592A

  • Ultrashort-focus projection curtain

    CN109343302A

  • Projection screen and projection device

    CN113741134A

  • Large-viewing-angle projection film and preparation method thereof

    CN116339061A

  • Fresnel projection curtain, roller body for production and manufacturing and using method

    CN117590681A